A new design of extensible solar-driven thermoelectric array with highly thermo/electro-conductive PCMs as solar receivers, thermal/electric bridges, and voltage fluctuation suppressors simultaneously. (15th January 2022) - Yuan, Tao; Shang, Jichao; Fang, Hanxiao; Liu, Haihui; Bao, Chenlu
Highlights: A new design of extensible solar-driven thermoelectric array with enhanced properties. The array's output voltage is 2.6-fold of that of conventional copper-bridged array. Combing solar revivers, bridges, and voltage fluctuation suppressors by using PCMs. PCMs with extremely high thermal (17.0 W/mK) and electrical conductivity (84.4 S/cm). A hypergravity-based compounding method to produce high-performance composite PCMs. Abstract: Solar-driven thermoelectric energy is a clean and renewable energy. Due to the limited irradiance of the sun, it is very important to obtain high photothermal conversion efficiency and low thermal resistance in solar-driven thermoelectric systems. Here we present a new design of extensible solar-driven thermoelectric array which combines the roles of solar receivers, thermal bridges, electric bridges, and voltage fluctuation suppressors together by using highly thermo/electro-conductive phase change materials (PCMs). The PCMs are prepared from worm graphite and paraffin wax by a hypergravity-based compounding method and have high thermal conductivity (17.0 ± 1.2 W/mK), electrical conductivity (84.4 ± 5.7 S/cm), and photothermal efficiency (95.4%). A single generator (1 pair p-n Bi2 Te3 ) under 1 sun irradiance has an output voltage of 4.8 mV. When the generators are integrated into an extensible array (15 pairs p-n Bi2 Te3 ) with the aid of PCMs, the output voltage is increased to 90.8 mV. It is 2.6-fold of that of conventional copper-bridged array, and 18-fold of that of a single generator. Meanwhile, output voltage fluctuation of the array can be suppressed by 30% when solar irradiance varies. Based on this design, arrays with a larger scale and better performance can be produced simply by adding generators and PCM bridges. This extendibility may create a new route to developing high-performance solar-driven thermoelectric systems.